Being targeted as a “severely overweight pregnant woman” —A qualitative interview study - Lauridsen, Drude S. (Health Expect, 2018)
BACKGROUND: Pregnant women with a body mass index (BMI) ≥ 30 kg/m(2) have been targeted in health‐care systems in many western countries as a high‐risk group. However, we have limited knowledge of the long‐term significance of this prenatal care policy. OBJECTIVE: To investigate accounts women give of their experiences of being targeted as severely overweight during pregnancy when they look back at the intervention 4‐5 years later. DESIGN: Interpretive analysis based on 21 semi‐structured interviews conducted 4‐5 years after the pregnancy with Danish mothers categorized as having a pre‐pregnancy BMI ≥ 30. FINDINGS: In the women's retrospective accounts three phases were identified and separated: (i) Being identified as a “severely overweight pregnant woman.” The women differed over whether they accepted this categorization, but all believed that an approach based on weight was acceptable. (ii) Encounters with health‐care professionals. The women differed here: some reported no negative experiences; others reported experiences of prejudice and silence. (iii) Reflections on long‐term outcomes. Most women reported that the interventions during their pregnancies did not lead to any lasting lifestyle change. The women disagreed over whether, in principle, pregnancy was a suitable time to be targeted. DISCUSSION AND CONCLUSION: Our study illustrates the importance of critically considering whether pregnancy is a suitable window of opportunity for obesity prevention, and shows that women's experiences should be examined in relation to each phase of intervention. More interdisciplinary studies are needed to map potential benefits and other consequences over the short‐ and long‐term.